(untitled) (One Health & Risk Management, 2023)
PROCEDURE FOR RAPID DETERMINATION OF CANDIDA SPECIES IN DRUGS Introduction. The contamination of drugs with unauthorized microorganisms poses a significant risk in the pharmaceutical industry, as it has the potential to compromise product integrity and jeopardize patient safety. Material and methods. The research was conducted using standard materials and reagents registered in the Republic of Moldova. The isolation and identification of Candida genus yeasts were performed concurrently using classical methods. The developed procedure was tested using both reference strains and clinical strains of Candida yeasts. Results. A procedure has been developed for the rapid determination of Candida yeasts. The method enables obtaining a preliminary result just 9 hours after inoculation of the examined material, a notable improvement compared to conventional methods. The procedure is characterized by its sensitivity, cost-effectiveness, simplicity, and accessibility, making it suitable for microbiological laboratories at various levels. Conclusions. The results derived from the study conducted in the microbiological monitoring of Candida yeasts hold the potential for application as a novel principle underlying drug quality control. This can contribute to the advancement of micromethods, autonomous diagnostic test systems, and new types of indicators for the rapid identification of microorganisms implicated in infectious pathology. These findings serve as a foundation for developing a comprehensive microbiological monitoring algorithm.